Compositional Format and Spell Sequencing in Early Versions of the Book of the Dead - Dorman, Peter F..
Recent studies of the early development of the Book of the Dead have tended to focus on the content of this group of spells, the objects on which the spells are written, the sequences in which they occur, and their early prototypes, which appear on Middle Kingdom coffins. The physical presentation of the first texts that can be described as fully in the Book of the Dead tradition, however, illustrates how scribes addressed the challenges of transmission of this mortuary corpus hand in hand with the evolution of novel burial practices in the Theban region beginning in the late Second Intermediate period, including the introduction of anthropomorphic coffins, linen shrouds, and papyrus rolls. Both hieratic and cursive hieroglyphic scripts were employed on these media, along with compositional formats suitable to them, as well as the appearance of scribal sketches that evolved into the vignettes for which the quintessential New Kingdom Books of the Dead are justly renowned. An “Ahmoside” sequencing tradition prior to the co-rule of Hatshepsut/Thutmose III is further defined, and the codicil to BD 72 is examined for its relation to the use of linen versus papyrus in Theban burials of the period. http://dx.doi.org/10.5913/jarce.55.2019.a003